Adapting a memory framework (source monitoring) to the study of closure processes - Foley, Mary Ann; Foley, Hugh J.; Korenman, Lisa M. (Memory & Cognition, 2002)
The present experiments adapt a memory framework (source monitoring) to the study of closure processes. Closure processes are invoked as explanatory mechanisms underlying the ability to identify objects under conditions of incomplete visual information. If closure processes are activated, filling in missing pieces of visual information, intriguing memory predictions follow. When making source judgments about the way in which visual information was experienced initially (e.g., complete or incomplete in form), a particular kind of memory error should be evident. Incomplete visual information should be remembered as complete in form, and indeed, this error is observed. The present experiments test alternative interpretations for the initial reports of this memory error in the context of a search task modeled after the Where's Waldo? children's books. The effects of several new factors (e.g., familiarity) are reported, and alternative interpretations for the bias to report complete are eliminated. Findings, therefore, have implications for understanding the mechanisms of closure processes, as well as for the source-monitoring framework itself.
Keywords: Cognitive science; Neuroscience